Analisis Total Productive Maintenance Menggunakan Metode Overall Equipment Effectivenes (OEE) dan Six Big Losses Pada Mesin Curing Tire Press di PT.XYZ - Siti Rahayu (Journal of Optimization System and Ergonomy Implementation, 2025)
This research was conducted at PT XYZ, a tire manufacturing company established in 1988 in Indonesia. The study focuses on the curing tire press machine, which has experienced high downtime issues. The purpose of this research is to analyze Total Productive Maintenance (TPM) using the Overall Equipment Effectiveness (OEE) method and calculate the Six Big Losses on the machine during the period of January to June 2023. Data was collected through observation, interviews, and literature review. The findings show that high breakdown frequency significantly impacted downtime and reduced production effectiveness. The OEE value of the curing tire press machine was 78.22%, which is below the global OEE standard of 85%. The largest factor hindering OEE achievement was Idling and Minor Stoppages, with a value of 21%. The proposed recommendations are expected to reduce downtime and improve machine performance, allowing PT XYZ to meet its production targets.